1993
DOI: 10.1227/00006123-199301000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Abnormality Disclosed by Computed Tomography after Mild Head Trauma

Abstract: We prospectively studied 712 consecutive patients during a 1-year period who presented with amnesia or loss of consciousness after nonpenetrating head trauma and who had a perfect Glasgow Coma Scale score of 15. Of the 67 (9.4%) patients with acute traumatic lesions disclosed by computed tomography (CT) of the head, 2 required neurosurgical intervention and 1 died. Four factors were statistically correlated (P < 0.05) with abnormal CT findings: Older age, white race, signs of basilar skull fracture, and being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Rates of intracranial injury were slightly lower than those quoted in previous studies (6.1–9.4%) 13 14 20. Those studies looked at all patients presenting with minor head injury, whereas our study focused on a potentially lower risk group presenting 4 h or more after injury.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Rates of intracranial injury were slightly lower than those quoted in previous studies (6.1–9.4%) 13 14 20. Those studies looked at all patients presenting with minor head injury, whereas our study focused on a potentially lower risk group presenting 4 h or more after injury.…”
Section: Discussionmentioning
confidence: 61%
“…However, a prospective study of 712 patients presenting to a US health centre with a GCS of 15 and a history of loss of consciousness or post-traumatic amnesia after blunt head trauma demonstrated that, regardless of age, mechanism of injury, or clinical findings, intracranial lesions cannot be completely excluded on the basis of risk factors alone. In that study, two patients (0.3%) required neurosurgical intervention 13. A second American study of 2143 head injury patients with GCS of 15 found that 3.7% with no risk factors for intracranial pathology had an abnormal CT. All patients requiring neurosurgical intervention had at least one other risk factor (such severe headache, nausea, vomiting, depressed skull fracture) 14…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…There has been some recent controversy over the management of minor head injuries, with some recommending that computed tomography or skull radiography be limited to high risk patients4 and others a more liberal use of early computed tomography 5 6. There has also been discussion as to the cost effectiveness of hospital admission for observation7 or routine scanning,8 given the low incidence of abnormalities detected that require operative intervention 9…”
Section: Discussionmentioning
confidence: 99%
“…Mild TBI generally follows a favourable course with abnormal CT scan findings seen only in 10% and surgical intervention needed in 1% of patients [2,3]. However, a subgroup of patients with mild injury and minimal findings on the initial CT scan may show further deterioration, because of delayed subdural or epidural haematoma [4], expansion of contusions [5] and presence of multiple lesions after trauma [6].…”
Section: Introductionmentioning
confidence: 99%